READING THE SIGNS OF THE TIMES - Canceran, Delfo C. (Asian Horizons, 2013)
The Vatican II Document Gaudium et Spes (The Church in the Modern World) obliges the church in reading of the signs of the times in relating with the modern world. Gaudium et Spes, # 4 states: To carry out such a task, the Church has always had the duty of scrutinizing the signs of the times and of interpreting them in the light of the Gospel. Thus, in language intelligible to each generation, she can respond to the perennial questions which people ask about this present life and the life to come, and about the relationship of the one to the other. We must therefore recognize and understand the world in which we live, its explanations, its longings, and its often dramatic characteristics.2 This document itemizes or enumerates the actions needed in reading the signs of the times such as “scrutinizing” and “interpreting”, “recognize” and “understand” as a duty of theChurch in relating with the world so that it can aptly respond to the relevant questions that people ask. Thus, the document tells us what to read – the signs – of the times. The document advises the people to read the signs of the times supposedly from the perspective of faith. Unfortunately, the document fails to show the people how to read these signs. Thus, there is a gap between the question on what and the question on how that the document glosses over. We are left groping in the dark on how to read these signs since they are not selfevident or self-explanatory signs; in fact, they are not simple but complex signs that we need to decipher. If this is the case, then we need a reading strategy in dealing with these signs. The absence of the how in reading the signs of the times in the document seems to suggest that reading the signs is taken for granted or the how of reading the times is entrusted to the people. In this way, the church seems to presume that the how of reading the signs of the times is unproblematic.